2021
DOI: 10.1007/s00395-021-00850-2
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII and PKA-dependent phosphorylation co-regulate nuclear localization of HDAC4 in adult cardiomyocytes

Abstract: Nuclear histone deacetylase 4 (HDAC4) represses MEF2-mediated transcription, implicated in the development of heart failure. CaMKII-dependent phosphorylation drives nucleus-to-cytoplasm HDAC4 shuttling, but protein kinase A (PKA) is also linked to HDAC4 translocation. However, the interplay of CaMKII and PKA in regulating adult cardiomyocyte HDAC4 translocation is unclear. Here we sought to determine the interplay of PKA- and CaMKII-dependent HDAC4 phosphorylation and translocation in adult mouse, rabbit and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…Furthermore, AngII/PE-induced [Ca 2+ ] i rise, as well as the phosphorylation of CaMKII in NRVMs, was significantly reduced by the TRPV4 antagonist. Previous studies have also shown that Ang II/PE promotes the phosphorylation of CaMKII, increases CaMKII activity, and subsequently mediates cardiac hypertrophy ( Helmstadter et al, 2021 ; Nakamura and Sadoshima, 2018 ; Tonegawa et al, 2017 ). However, the calcineurin/NFAT pathway may play a more important role in AngII-induced cardiac hypertrophy ( Yu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, AngII/PE-induced [Ca 2+ ] i rise, as well as the phosphorylation of CaMKII in NRVMs, was significantly reduced by the TRPV4 antagonist. Previous studies have also shown that Ang II/PE promotes the phosphorylation of CaMKII, increases CaMKII activity, and subsequently mediates cardiac hypertrophy ( Helmstadter et al, 2021 ; Nakamura and Sadoshima, 2018 ; Tonegawa et al, 2017 ). However, the calcineurin/NFAT pathway may play a more important role in AngII-induced cardiac hypertrophy ( Yu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 89%
“…Although chronic β-adrenergic tone is readily implicated in the development of cardiac pathologies, while acute effects are known for instantaneous regulation of cellular Ca 2+ cycling and contractility, little is known about the role of β-adrenergic signaling in preventing gene reprograming under short-term physiological stress. We previously showed that ISO keeps histone deacetylase 4 (HDAC4) localized in the nucleus in the very early response to physiological challenge [ 37 ]. Maccari et al showed that β-adrenergic signaling also prevents the upregulation of β-myosin heavy chain (β-MHC), and both effects are associated with preventing cardiac dysfunction [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that ISO keeps histone deacetylase 4 (HDAC4) localized in the nucleus in the very early response to physiological challenge [ 37 ]. Maccari et al showed that β-adrenergic signaling also prevents the upregulation of β-myosin heavy chain (β-MHC), and both effects are associated with preventing cardiac dysfunction [ 37 , 38 ]. Our present data identify a novel β-adrenergic-signaling-dependent mechanism for controlling transcriptional reprograming during short-term increase in workload demands of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of FKN to its receptor CX3CR1 increases intracellular secretion of adenosine, which binds to its receptor and presents key biological activities and pharmacological characteristics in the hippocampus [ 42 ]. We inferred that, under diabetic condition, (a) abnormal increase in A2AR density promotes the release of a large amount of D-serine, an endogenous ligand for NR, resulting in excessive activation of NR on neurons [ 43 ]; (b) adenosine binds to the A1R, which leads to decreased BDNF secretion and neurotrophic deficiency [ 44 ]; and (c) inhibition of the A3R on neuronal membrane induces NMDA channel opening and increases intracellular Ca 2+ concentration, resulting in Ca 2+ /CaMKII-dependent inhibition [ 45 ]. Therefore, FKN can regulate the density changes of NR receptor subtypes NR2A and NR2B through the FKN/CX3CR1 signaling pathway, leading to NR activation and thus mediating the abnormal change of hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%